Inter-sectoral Linkages and Local Content in Extractive Industries and Beyond : The Case of Sao Tome and Principe - Segura Vasi, Alonso (IMF Working Papers; Working Paper ;, 2007)
This paper attempts to offer specific inputs to the debate on local content promotion in the oil industry, using the specific case of Sao Tome and Principe as point of reference. Our approach emphasizes inter-sectoral linkages and institutional pre-conditions for local content promotion. Based on an Input-Output description of the economy, we quantify the consistency between the prospective oil sector development and the growth of other sectors of the economy. We also assess a number of sectoral policies and "niche" activities within the oil industry that would maximize the local benefits from oil exploration.